Knowledge of Emergency Contraceptive Pills among Hungarian Women Presenting for Induced Abortion or Seeking Emergency Contraception - Kozinszky, Z.; Devosa, I.; Fekete, Z.; Szabó, D.; Sikovanyecz, J.; Pásztor, N.; Keresztúri, A. (Geburtshilfe und Frauenheilkunde, 2016)
Aim: To compare the differences in contraceptive characteristics and the knowledge of emergency contraception (ECP) among women who used ECP after unprotected intercourse and those who sought an abortion.Methods: A questionnaire survey was conducted in a Hungarian university hospital among women for whom ECP was prescribed after unprotected intercourse (n = 940) as well as women who presented for the termination of pregnancy (n = 1592) between January 1, 2005 and November 20, 2006. Their knowledge of ECP and their experience with and attitudes toward ECP use were targeted.Results: The availability of ECP was well known (87.9 %), but it was still greatly underutilized: applied by only 13 of the 1592 women who resorted to abortion. Primarily, the ECP group consisted of those who experienced a condom failure significantly more often (odds ratio [OR] = 4.1), followed by those cases where ECP applications was a consequence of not using any kind of contraception (OR = 3.8). Fewer than one third (32 %) of the abortion seekers had previously used ECP, and only one fifth knew how to obtain it. Appropriate awareness of ECP was influenced by information obtained from health-care providers (adjusted odds ratio [AOR] = 3.93) or school education (AOR = 1.82).Conclusions: More thorough education is needed to provide a deeper knowledge of ECP use during contraceptive counseling for women seeking abortion, including those contraceptive mishaps where unintended pregnancy can be prevented by ECP.
Keywords: emergency contraceptive pill; women requesting pregnancy termination